A tensor-based modelling and simulation method for multibody system. Issue 4 (12th June 2017) - Shen, Fan; Rong, Siyuan; Cui, Naigang; Kong, Xianren
Abstract : Purpose: The purpose of this paper is to provide a method with convenient modelling as well as precise computation to the research of complex multi-body system, such as robot arms and solar power satellite. Classical modelling method does not always fit these two requirements. Design/methodology/approach: In this paper, tensor coordinates (TC) and homogeneous tensor coordinates (HTC) method with gradient components are developed, which also have a convenient interface with classical theory. Findings: The HTC proved its precision and effectiveness by two examples. In HTC model, equations have a more convenient form as matrix and the results coincide well with classical one. Research limitations/implications: There is no plenty detailed operations supported in mathematics yet, which may be developed in further research. Practical implications: With TC/HTC method, the research work can be separated more thoroughly: a simpler modelling work is left to scientists, when more computing work is handed to the computers. It may ease scientists' brains in multibody modelling. Originality/value: The HTC method has the advantages of absolute nodal coordinate formulations, tensor and homogeneous coordinate (HC) and it may be used in multibody mechanics, or other related engineerings.